2023
DOI: 10.2174/1871527321666220512155811
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Amphetamine use in Stroke Recovery Combined with Rehabilitative Training and Brain Stimulation

Abstract: Stroke is a physiological disorder involving a prolonged local interruption of cerebral blood flow. It leads to massive neuronal death and causes short-term or long-lasting functional impairment. Most stroke victims regain some neural function weeks or months following a stroke, but this recovery can plateau six months or more after the injury. The goal of stroke therapy is the rehabilitation of functional capabilities, especially those affecting the patient’s autonomy and quality of life. Recent clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 144 publications
2
3
0
Order By: Relevance
“…One of the factors shown to initiate Nrf2 translocation is BDNF (Bruna et al, 2018;Davies et al, 2021), whose expression is proven to be modulated by rTMS (Stevanovic et al, 2019). Our results demonstrated TMS-mediated elevation of both Nrf2 and BDNF, which might partially explain the improvement of overall oxidative status (Numakawa et al, 2018;Liang et al, 2021;Uzair et al, 2022. ) following STZ administration.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…One of the factors shown to initiate Nrf2 translocation is BDNF (Bruna et al, 2018;Davies et al, 2021), whose expression is proven to be modulated by rTMS (Stevanovic et al, 2019). Our results demonstrated TMS-mediated elevation of both Nrf2 and BDNF, which might partially explain the improvement of overall oxidative status (Numakawa et al, 2018;Liang et al, 2021;Uzair et al, 2022. ) following STZ administration.…”
Section: Discussionsupporting
confidence: 53%
“…In developing antioxidant therapies for neurological disease, special attention should be given to the brain's unique vulnerability of the brain to oxidative insults and its architecture (Birngruber et al, 2013). rTMS has been postulated as a promising therapeutic approach in the treatment of neurodegenerative disorders, through the production of complex neurobiological effects such as induction of early genes, changes in Ca 2+ dynamics, reduction of oxidative stress and inflammation, and activation of neurotrophic factors (Uzair et al, 2022). Herein, we applied iTBS, a highly efficient protocol of rTMS, to evaluate its effect on oxidative stress and the promotion of antioxidative capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of physical function, survivors had improved their status at three months after discharge compared with that at discharge. This finding of this study is similar to that in prior studies, as stroke recovery improves during this period after discharge [38][39][40]. Thus, the results of the score of each FIM item in SEM-3M in this study suggested moving toward recovery when compared with the score in SEM-D.…”
Section: Discussionsupporting
confidence: 90%
“…Functional recovery was mostly unchanged compared with at three months after discharge. Stroke recovery tends to improve sharply until three months from stroke onset, and only moderately thereafter [38][39][40].…”
Section: Discussionmentioning
confidence: 99%